Stable softening bioelectronics: A paradigm for chronically viable ester-free neural interfaces such as spinal cord stimulation implants. (October 2021) - Garcia-Sandoval, Aldo; Guerrero, Edgar; Hosseini, Seyed Mahmoud; Rocha-Flores, Pedro E.; Rihani, Rashed; Black, Bryan J.; Pal, Ajay; Carmel, Jason B.; Pancrazio, Joseph J.; Voit, Walter E.
Abstract: Polymer toughness is preserved at chronic timepoints in a new class of modulus-changing bioelectronics, which hold promise for commercial chronic implant components such as spinal cord stimulation leads. The underlying ester-free chemical network of the polymer substrate enables device rigidity during implantation, soft, compliant, conforming structures during acute phases in vivo, and gradual stabilization of materials properties chronically, maintaining materials toughness as device stiffness changes. In the past, bioelectronics device designs generally avoided modulus-changing and materials due to the difficulty in demonstrating consistent, predictable performance over time in the body. Here, the acute, and chronic mechanical and chemical properties of a new class of ester-free bioelectronic substrates are described and characterized via accelerated aging at elevated temperatures, with an assessment of their underlying cytotoxicity. Furthermore, spinal cord stimulation leads consisting of photolithographically-defined gold traces and titanium nitride (TiN) electrodes are fabricated on ester-free polymer substrates. Electrochemical properties of the fabricated devices are determined in vitro before implantation in the cervical spinal cord of rat models and subsequent quantification of device stimulation capabilities. Preliminary in vivo evidence demonstrates that this new generation of ester-free, softening bioelectronics holds promise to realize stable, scalable, chronically viable components for bioelectronic medicines of the future.